Comparison of the performance and durability of PEM fuel cells with different Pt-activated microporous layers. (17th May 2021) - Ivanova, Nataliya A.; Spasov, Dmitry D.; Zasypkina, Adelina A.; Alekseeva, Olga K.; Kukueva, Elena V.; Vorobyeva, Ekaterina A.; Kudinova, Ekaterina S.; Chumakov, Ratibor G.; Millet, Pierre; Grigoriev, Sergey A.
Abstract: We report on a comparative study of the performance level of H2 /O2 PEM fuel cells in which the catalytic layers containing Pt nanoparticles were deposited on the microporous layer side of gas diffusion electrodes, using three different deposition techniques: (i) by magnetron sputtering, (ii) by impregnation followed by chemical reduction (using either ethylene glycol or hydrogen or sodium borohydride as reducing agent), and (iii) by spraying a catalytic ink (containing either Pt/C or bulk Pt particles). The microstructure and chemical composition of the different catalytic layers has been determined by SEM, TEM, XRD and XPS analysis. Their electrochemical surface areas have been determined by cyclic voltammetry. The i-V curves have been measured and compared. A durability stress test based on cycles of potential was used to assess the degradation rate of the different catalytic layers and to rank performance. Graphical abstract: Image 1 Highlights: Ethylene glycol is the most effective Pt reducing agent for impregnation method. Pt particles supported on microporous layers demonstrate improved durability. A strong interaction between Pt active sites and carbon atoms is observed. Pt particles supported on microporous layers and on carbon have similar structure.